Water footprint of protein formation of six field crop species - M. Kassai, Katalin; Tarnawa, Ákos; Jolánkai, Márton (GEORGIKON FOR AGRICULTURE, 2019)
Plant growth and development is driven by various physiological processes in which water availability is a most profound factor. An assessment study has been done at the Szent István University, Gödöllő to evaluate and identify the water footprint of protein yield of field crop species. Six field crop species (Sugar beet Beta vulgaris, winter barley Hordeum vulgare, winter wheat Triticum aestivum, maize Zea mays, potato Solanum tuberosum, and alfalfa Medicago sativa) were involved in the study. Evapotranspiration patterns of the crops studied have been monitored and physiologically reliable protein ranges within crop yields were identified. The results obtained seems to prove that water footprint of cereals was the lowest, however maize values were highly affected by the high variability of protein yield. Alfalfa, potato and sugar beet water footprints were in accordance with their evapotranspiration patterns.
Keywords: water footprint; evapotranspiration; protein; field crop species